The use of multiplex-PCR method in identification of Candida species from vaginal candidiasis patients - SUSILAWATI; KEMAS YA’KUB RAHADIYANTO; MUHAIMIN RAMDJA; THEODORUS; Hermansyah Hermansyah (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Susilawati, Rahadiyanto KY, Ramdja, Theodorus, Hermansyah. 2019. The use of multiplex-PCR method in identification of Candida species from vaginal candidiasis patients. Biodiversitas 20: 3063-3069. Vaginal Candidiasis is an infection caused by a yeast called Candida which may be resulted in different virulences, thus leading to a varied drug of choice for therapy. The objective of this study was to determine the sensitivity and specificity of multiplex-PCR test in detecting Candida species in women with clinical diagnosis of vaginal candidiasis. There were 79 vaginal swab samples which fulfill inclusion criteria. Samples were cultured at ASD media for isolation of Candida spp. Identification of Candida spp. was conducted using both biochemical fermentation and multiplex-PCR methods. Primers pairs used in multiplex-PCR were universal primer ITS1 and ITS2, and specific primer CA3 and CA4. The identification test of multiplex-PCR resulted in Candida krusei: sensitivity: 100%, specificity:61,1%, Positive Prediction Value (PPV):63.2%, Negative Prediction Value (NPV): 100%; C. glabrata: sensitivity:0%, specificity: 100% PPV: 0% NPV: 76.7%; C. tropicalis: sensitivity:100%, spesificity:100%, PPV: 100% NPV: 100%; C. albicans: sensitivity: 33.3%, specificity: 100%, PPV: 100%, NPV: 93.1% and C. stellatoidea: sensitivity:: 100%, specificity:92.6%, PPV: 60%, NPV: 100%. These results suggested that multiplex-PCR method becomes a rapid alternative in identifying species of Candida due to its high sensitivity and high specificity.